2020
DOI: 10.24315/tred.562045
|View full text |Cite
|
Sign up to set email alerts
|

Dolaylı veya Doğrudan Düzeltme Geribildirimi: Bir Eylem Araştırması

Abstract: Gelişimi yabancı dil öğrenenlere hem akademik hem de iletişimsel anlamda katkıda bulunan yazma becerisi ve "iyi kurgulanmış bir yazılı metni" oluşturan bileşenler, araştırmacıların on yıllardır dikkatini çeken önemli konular arasında olmuştur. En genel şekliyle yazma, yararlı bir dil pratiği biçimi olmasının yanı sıra, bir yazarın fikirleri iletme şeklidir. Bununla birlikte, düşünce süreçleri yoluyla fikir oluşturmak ve bunları başarılı bir şekilde iletmek için anlaşılır cümlelere ve paragraflara ihtiyaç bulun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Lastly, Berkant, Derer and Derer (2020) found that, based on their quantitative data, the most effective type of feedback is the underlined feedback while the qualitative findings indicated that the coded error correction accompanied with explanation is the most effective type. Similarly, Uzun and Köksal (2020) tried to find out whether direct or indirect written CF was more effective for writing errors. The findings of the study revealed that the participants benefited from both types of written corrective feedback while indirect feedback turned out to be more appropriate for in-class practices as it required direct feedback for final drafts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, Berkant, Derer and Derer (2020) found that, based on their quantitative data, the most effective type of feedback is the underlined feedback while the qualitative findings indicated that the coded error correction accompanied with explanation is the most effective type. Similarly, Uzun and Köksal (2020) tried to find out whether direct or indirect written CF was more effective for writing errors. The findings of the study revealed that the participants benefited from both types of written corrective feedback while indirect feedback turned out to be more appropriate for in-class practices as it required direct feedback for final drafts.…”
Section: Discussionmentioning
confidence: 99%
“…However, the qualitative data indicated that the coded error correction accompanied with explanation is the most effective type. Uzun and Köksal (2020) tried to find out whether direct or indirect written CF was more effective for writing errors. The participants were 28 students studying English at the preparatory school of a state university in Turkey.…”
Section: Literature Reviewmentioning
confidence: 99%